Exciplex-forming cohost systems with highly twisted hexaphenylbenzene-core donors for high-efficiency orange and red OLEDs. Issue 12 (20th September 2022) - Chen, Yi-Sheng; Wei, Wei-Chih; Chen, Hao; Tsai, Tsung-Lin; Kung, Yu-Cheng; Hung, Wen-Yi; Wong, Ken-Tsung
Abstract : Two hexaphenylbenzene (HPB)-based donors (D), CzTT and DDT-HPB, are blended with the triazine-centered acceptors (A) CN-T2T and PO-T2T to examine exciplex formation. Abstract : Two hexaphenylbenzene (HPB)-based donors (D), CzTT and DDT-HPB, are blended with the triazine-centered acceptors (A) CN-T2T and PO-T2T to examine exciplex formation. The highly twisted conformation of the HPB core allows CzTT and DDT-HPB to exhibit high triplet states and excellent thermal stability. The red-shifted emission together with delayed fluorescence observed by transient photoluminescence analyses reveal effective exciplex formation with thermally activated delayed fluorescence (TADF) features for the CzTT : PO-T2T, DDT-HPB : CN-T2T and DDT-HPB : PO-T2T blends. The exciplex emission wavelength can be modulated by energy level alignment at the donor and acceptor interface. The device with the CzTT : PO-T2T (1 : 1) blend as the emission layer (EML) gives sky-blue electroluminescence (EL) with a λ max of 480 nm and external quantum efficiency (EQE) of 9.8%, while the orange device employing the DDT-HPB : PO-T2T (1 : 1) blend exhibits an EL λ max of 580 nm and EQE of 5.2%, revealing the influence of the donor on the device characteristics. Importantly, reducing the acceptor strength from PO-T2T to CN-T2T, the yellow device employing the DDT-HPB : CN-T2T (2 : 1) blend as the EML exhibits an EL λ max of 550 nm and EQE of 8.9%, which maintains an EQE of up to 8.8% at 1000 nits. To further harness the excitons formed in the exciplex-forming blends, two D–A–D-type fluorescence emitters, NZDSF and DPyCN, were introduced as dopants. The good spectral overlap ensures efficient Förster energy transfer (FRET) between the exciplex-forming systems and the fluorescent dopants. The orange-red device employing the EML composed of 3 wt% NZDSF doped in the CzTT : PO-T2T (1 : 1) cohost exhibits an EL λ max of 615 nm and EQE of 7.3%, while the deep-red device with 3 wt% DPyCN doped in the DDT-HPB : CN-T2T (2 : 1) cohost as the EML affords an EL λ max of 667 nm and EQE of 5.5%. Our study shows that the combination of an exciplex cohost and a judiciously selected D–A–D-type fluorescence emitter is an effective strategy for developing high-efficiency OLED devices with all fluorescent materials.